A comparative analysis of trends of echocardiographic parameters in double valve replacement cases involving the use of Del Nido’s and Saint Thomas’ cardioplegia for myocardial protection: A single-center study - Archit Patel; Kartik Patel; Praveen Nayak; Shobhit Mathur (Heart India)
Background: Del Nido and St. Thomas both cardioplegia solutions are used in valvular heart surgery for myocardial protection. Previously, there have been studies comparing intraoperative and postoperative parameters and outcomes. Here, we highlight the comparison of trends of echocardiographic parameters in double valve replacement cases. Materials and Methods: In this retrospective study, 70 double valve replacement cases (35 in each group) were selected from 2022 to 2023. All cases were operated in the same surgical unit. Preoperative, intraoperative, and postoperative data were collected from hospital records. Echocardiographical data were collected from preoperative echo, intraoperative trans-esophageal echocardiography, and postoperative echo in the intensive care unit done on the next day of surgery and at 6-month follow-up. Results: Baseline demographic characters were statistically nonsignificant in both groups. In postoperative period, there was a statistically significant difference was found in left ventricular ejection fraction/right ventricular systolic pressure and tricuspid annular systolic plane excursion in both the groups compared to preoperative values. However, the difference in these parameters between both groups came out statistically nonsignificant at intro, postoperative, and at 6-month follow-up. Conclusion: Despite having different cardioplegia used, postoperative dysfunction of both left ventricular and right ventricular is inevitable Hence, we conclude that both the solutions can be used with equal efficacy and safety in terms of dysfunction caused.